2006
DOI: 10.1086/501056
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Behavior Influence Lactation Efficiency in Northern Elephant Seals (Mirounga angustirostris)

Abstract: The efficiency with which mothers convert acquired energy into milk is a key determinant of the magnitude of parental in vestment in mammals; however, the mech~isms underlying lactation efficiency are poorly understood. Investigations on northern elephant seals have shown lactation efficiency, mea sured as the proportion of total energy expenditure that goes to the pup as milk, increases with age. In a cross-sectional study the physiological and behavioral determinants of lactation ef ficiency were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…This phenomenon may be exclusive to fasting seal pups because lipase expression decreases with age in skeletal muscle of Weddell seals (Kanatous et al, 2008) and LPL activity decreases in blubber and mammary tissue of lactating adult female northern elephant seals (McDonald and Crocker, 2006). Despite the increased activity of plasma lipases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be exclusive to fasting seal pups because lipase expression decreases with age in skeletal muscle of Weddell seals (Kanatous et al, 2008) and LPL activity decreases in blubber and mammary tissue of lactating adult female northern elephant seals (McDonald and Crocker, 2006). Despite the increased activity of plasma lipases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although shortterm elevations of NEFA are known to stimulate insulin secretion (Bollheimer et al, 1998), a considerable amount of research has shown that chronically elevated NEFA are the initiating cause of an impairment in insulin signal transduction (Boden and Laakso, 2004;Yu et al, 2002). Previous research has shown that fasting elephant seals have elevated NEFA (1.0-3.2 mmol l -1 ) (Castellini et al, 1987;Houser et al, 2007;McDonald and Crocker, 2006) in comparison to other non-fasting adapted species (e.g. 0.14 mmol l -1 in humans) (Fery et al, 1990).…”
Section: Mechanisms For Altering Insulin Secretion and Sensitivitymentioning
confidence: 99%
“…During the breeding season, female NES give birth to a single pup and nurse the pup for ∼26 days while abstaining completely from nutrient intake. This intense, short investment period is characterized by rapid nutrient transfer from mother to pup in the form of milk that is ∼25% lipid in early lactation, increasing to >55% lipid shortly before weaning (McDonald and Crocker, 2006;Fowler et al, 2016;Crocker et al, 2001) (Table 1, Fig. 1).…”
mentioning
confidence: 99%